Resenhas acadêmicas: caracterização do gênero nas áreas de Linguística, Literatura e História, à luz da Linguística Sistêmico-Funcional - Silva, Aline Cristina Flávio da (2014)
This research is part of SAL Project - Systemis Across Languages - which has been developed by researchers from China, Argentina, Mexico and Thailand who analyse language in use having specific texts as a starting point in order to find out patterns as well as varieties of use. In Brazil, researches have focused on academic papers. Therefore, in order to contribute to the researchers developed in Brazil, the objective of this study is to identify the uses of verbal and mental processes in reviews published in the areas of Linguistics, Literature and History, analyse the patterns of realization of these processes in order to better understand how the reviewer conveys his description/evaluation of a certain book, and the role of modal adjuncts in meaning making. Systemics Functional Linguistics is the main theoretical and methodological framework (Halliday, 1985, 1994; Halliday & Matthiessen, 1999, 2004), which focus is language in use in different contexts. The software WordSmith Tools 5.0 allowed 45 reviews of Linguistics, 47 reviews of Literature and 46 reviews of History, all of them available electronically and qualified as Qualis A1 and A2 to be processed so that data were organized for analysis. Based on the transitivity system through which the ideational metafunction is accessed, the most frequent verbal and mental processes in the reviews from the three different areas were selected and their similarities and differences were compared. It was observed that the uses of verbal and mental processes in the reviews from the three areas mentioned are, most of the time, associated to a higher engagement of the reviewer who prioritizes a more elaborated use of the language, making use of verbiage which construes the content of what is said and reduces the clause. As far as choices of Sayers and Sensers are concerned, there is evidence of high interaction with the reader. Concerning the interpersonal metafunction, modal adjuncts of polarity, intensity and temporality were identified in the corpora. They accompany verbal and mental processes and highlight the engagement of the reviewer with his text when negotiating with the reader. This research is expected to contribute to the studies about the genre review written in Portuguese, providing background for those who intend to produce this genre in the areas hereby mentioned